Challenges and Security Risks in the Red Sea: Impact of Houthi Attacks on Maritime Traffic - Emilio Rodriguez-Diaz; J. I. Alcaide; R. Garcia-Llave (Journal of Marine Science and Engineering)
This study examines the significant impact of Houthi insurgent activities on maritime traffic within the strategic Red Sea and Suez Canal routes, essential conduits for global trade. It explores the correlation between regional instability, exemplified by Houthi actions from 19 November 2023 to 5 February 2024, and changes in maritime traffic patterns and operational efficiency. This study seeks to answer a critical question in transport geography: how does regional instability, exemplified by Houthi insurgent activities, affect the maritime traffic patterns and operational efficiency of the Red Sea and Suez Canal? Using descriptive statistics, qualitative analysis, and geospatial methods, this research highlights recent trends in maritime traffic and incidents, revealing spatial and geopolitical challenges in this crucial trade route. The findings indicate a notable decline in maritime activity in the Gulf of Aden and Suez Canal due to security concerns from Houthi attacks, prompting a significant shift to alternative routes, particularly around the Cape of Good Hope. This shift underscores the broader implications of regional instability on global trade and the importance of maintaining an uninterrupted maritime flow. This study also emphasizes the economic ramifications, such as increased operational costs and freight rates due to longer transit times and enhanced security measures. This research concludes with a call for improved maritime security protocols and international cooperation to protect these strategic maritime pathways. It contributes to the discourse on transport geography by quantifying the direct impacts of regional conflicts on maritime logistics and proposing strategies for future resilience, highlighting the interconnected nature of global trade and security and the need for collective action against evolving geopolitical challenges.